THE EFFECT OF TEACHING STYLE ON STUDENTS’ ENGLISH PROFICIENCY AT SMA NEGERI 5 BAUBAU - Hidayat, Hidayat (English Education Department, 2024)
Problem statement of this research was whether there is any positive and significant effect of teaching style on students' English proficiency at SMA Negeri 5 Baubau. Objective of this research was to find out the effect of teaching style on students' English proficiency at SMA Negeri 5 Baubau. This research used a quantitative approach applying ex post facto method. Population in this research was all grade eleven students of SMA Negei 5 Baubau consisted of 192 students. The sample was taken by using simple random sampling technique namely 50 students at grade eleven of SMA Negeri 5 Baubau. Instrument of this research were questionnaire and test. Research outcomes indicate that score of F count was 0.050 with the significant value was 0.825. Because score of F count was greater than F table and score of significant was greater than α (0.05). It means that there was not any positive and significant effect of teaching style on students’ English proficiency at SMA Negeri 5 Baubau